Silicone based dielectric elastomer strip actuators coupled with nonlinear biasing elements for large actuation strains. (5th June 2018) - Hau, S; Bruch, D; Rizzello, G; Motzki, P; Seelecke, S
Abstract: There are two major categories of dielectric elastomer actuators (DEAs), which differ from the way in which the actuation is exploited: stack DEAs, using the thickness compression, and membrane DEAs, which exploit the expansion in area. In this work we focus on a specific type of membrane DEAs, i.e., silicone-based strip-in-plane (SIP) DEAs with screen printed electrodes. The performance of such actuators strongly depends on their geometry and on the adopted mechanical biasing system. Typically, the biasing is based on elastomer pre-stretch or on dead loads, which results in relatively low actuation strain. Biasing systems characterized by a negative rate spring have proven to significantly increase the performance of circular out-of-plane DEAs. However, this kind of biasing has never been systematically applied to silicone SIP DEAs. In this work, the biasing design based on negative rate springs is extended to strip DEAs as well, allowing to improve speed, strain, and force of the resulting actuator. At first, the DEAs are characterized under electrical and mechanical loading. Afterwards, two actuator systems are studied and compared in terms of actuation strain, force output, and actuation speed. In a first design stage, the DEA is coupled with a linear spring. Subsequently, the membrane is loaded with a combination of linear and nonlinear spring (working in a negative stiffness region). The resulting stroke output of the second systems is more than 9 times higher in comparison to the first one. An actuation strain of up to 45% (11.2 millimeter) and a force output of 0.38 Newton are measured. A maximum speed of 0.29 m s −1 is achieved, which is about 60 times faster than the one typically measured for similar systems based on VHB.